2008
DOI: 10.1038/npp.2008.138
|View full text |Cite
|
Sign up to set email alerts
|

Δ9-Tetrahydrocannabinol Induces Dopamine Release in the Human Striatum

Abstract: The influence of cannabis on mental health receives growing scientific and political attention. An increasing demand for treatment of cannabis dependence has refueled the discussion about the addictive potential of cannabis. A key feature of all addictive drugs is the ability to increase synaptic dopamine levels in the striatum, a mechanism involved in their rewarding and motivating effects. However, it is currently unknown if cannabis can stimulate striatal dopamine neurotransmission in humans. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(189 citation statements)
references
References 55 publications
8
169
2
2
Order By: Relevance
“…DRD2 encodes the D2 dopamine receptor and dopamine has previously been implicated in both MDD and addition phenotypes, via its role in motivation and reward [47] and the effects of abused substances (including cannabis) on dopamine levels in the nucleus accumbens [48,49]. NCAM1 encodes a brain-expressed cell adhesion protein [50], known to be involved in the development of the nervous system and neuroplasticity (important in learning and memory, as reviewed by [51]).…”
Section: Replication Of Previous Findingsmentioning
confidence: 99%
“…DRD2 encodes the D2 dopamine receptor and dopamine has previously been implicated in both MDD and addition phenotypes, via its role in motivation and reward [47] and the effects of abused substances (including cannabis) on dopamine levels in the nucleus accumbens [48,49]. NCAM1 encodes a brain-expressed cell adhesion protein [50], known to be involved in the development of the nervous system and neuroplasticity (important in learning and memory, as reviewed by [51]).…”
Section: Replication Of Previous Findingsmentioning
confidence: 99%
“…In humans, PET studies have shown that several drugs [stimulants (Drevets et al 2001;Volkow et al 1999b), nicotine (Brody et al 2009), alcohol (Boileau et al 2003), and marijuana (Bossong et al 2009)] increase DA in dorsal and ventral striatum (where the NAc is located).…”
mentioning
confidence: 99%
“…Whereas there is general consensus on the primary involvement of DA in the mechanisms supporting METH-induced acute psychotic states [152,153], the role of this neurotransmitter in cannabis-induced psychosis is more controversial. It has been reported that, in schizophrenia patients, doses of THC that exacerbate psychotic symptoms are associated with a rapid reduction of D 2 receptor binding in the ventral striatum and precommissural dorsal putamen [154,155]. However, similar phenomena were not observed in healthy volunteers [156].…”
Section: Effects Of Meth and Cannabis On Schizophreniamentioning
confidence: 91%